Strategies for Improving the Welfare of Honorary Teachers: a Case Study in Elementary Schools - Rahma Yulida; Wirda Nursanti (PT. ALHAFI BERKAH INDONESIA, 2025)
This study aims to identify and analyze the strategies implemented by elementary schools in suburban areas to improve the welfare of honorary teachers. The background of this research stems from the reality of the low welfare of honorary teachers in Indonesia, particularly in non-urban areas, which affects their motivation and the quality of education. This study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and document analysis, with research subjects consisting of honorary teachers, school principals, and school committee members. The results of the study indicate that several strategies have been adopted by schools to enhance the welfare of honorary teachers, including: providing non-formal additional incentives from the school committee, involving teachers in school-based activity programs, facilitating training and certification, and conducting advocacy efforts to local governments. These strategies have had positive impacts, both economically and psychologically, such as improved work motivation, loyalty, and active participation of honorary teachers in school activities. However, the implementation of these strategies still faces several challenges, such as budget constraints and the lack of comprehensive policy support from the government. This study recommends the importance of collaboration among schools, communities, and governments in formulating policies that are more supportive of honorary teacher welfare, recognizing them as a vital part of the national education system.